The Relationship Between Oil Prices and Stock Prices of the European Renewable Energy Companies: A Vector Autoregressive Analysis - Slatina, Enis; Lazović-Pita, Lejla; Abdić, Ademir; Abdić, Adem (Naše gospodarstvo/Our economy, 2023)
The objective is to examine the potential relationship between Brent crude oil futures prices and the index of the European renewable energy companies. After the overview of the European legislation and the most recent literature review on the topic, the article deploys a method of the Vector Autoregressive Model (VAR). The analysis includes weekly data over eight years (2015-2022). Our results indicate a positive correlation between Brent crude oil futures prices and the value of the European Renewable Energy Total Return (ERIX) index. The estimated bivariate VAR model indicates a statistically significant relationship, meaning that past values of the ERIX Index may be used to predict future Brent crude oil prices in the long run. Considering the most recent systemic disturbance in the world’s commodity market, future research should consider longer time series and possible relationships of other macroeconomic factors.